Clinical significance of the C-reactive protein-to-bilirubin ratio in patients with ulcerative colitis - Huang, Xijing; Liu, Ya; Zhou, Zhou; Pan, Yan; Zhang, Yinghui; Gao, Caiping; He, Chong (Frontiers in Medicine, 2023)
Ulcerative colitis (UC) is a chronic relapsing remitting disease of the colon.Appropriate monitoring of the disease status is necessary for patients to adopt optimal therapy and obtain a better prognosis. Finding an ideal non-invasive biomarker, which is suitable for long-term monitoring in clinical settings, will bring a significant benefit in the individualized management of patients with UC. The aim of this study is to determine the clinical significance of a novel optimizing serological biomarker by integrating C-reactive protein (CRP) and bilirubin levels in monitoring disease activity. Here, a total of 182 patients with UC were retrospectively enrolled. Clinical characteristics and laboratory parameters of subjects were retrieved from the electronic medical record database of our hospital. The CRP-to-bilirubin ratio (CBR) was computed for clinical activity of UC defined by the partial Mayo score, and endoscopic activity by the Mayo endoscopic score (MES). CBR was significantly elevated in patients with UC than that in healthy controls. Patients with clinically or endoscopically active UC showed evidently higher CBR levels compared to those with inactive disease, even in a subset of patients with normal CRP levels. Receiver operating characteristic (ROC) analysis showed that the area under the curve (AUC) of CBR was higher than that of CRP or bilirubin alone for determining clinical remission and endoscopic mucosal improvement. Furthermore, CBR levels were significantly decreased when patients achieving mucosal improvement compared with 4 when they had active endoscopic inflammation. CBR could be useful to reflect disease activity in patients with UC.